Triggermuscle: Exploring Weight Perception for Virtual Reality Through Adaptive Trigger Resistance in a Haptic VR Controller - Stellmacher, Carolin; Bonfert, Michael; Kruijff, Ernst; Schöning, Johannes (Frontiers in Virtual Reality, 2022)
It is challenging to provide users with a haptic weight sensation of virtual objects in VR since current consumer VR controllers and software-based approaches such as pseudo-haptics cannot render appropriate haptic stimuli. To overcome these limitations, we developed a haptic VR controller named Triggermuscle that adjusts its trigger resistance according to the weight of a virtual object. Therefore, users need to adapt their index finger force to grab objects of different virtual weights. The dynamic and continuous adjustment is enabled by our spring mechanism inside the casing of an HTC Vive controller. In two user studies, we explored the effect on weight perception. Our findings show that adaptive trigger resistance can provide haptic weight cues in VR, but at the same time, highlight current limitations in sensing the resistance. We discuss possible confounding factors, how to overcome them in future research and the pros and cons of this novel technology.